Isolation of Betulinic Acid and 2,3-Dihydroxyolean-12-en-28-oic Acid from the Leaves of Callistemon linearis - Haque, Ayesha; Siddiqi, M Mahboob Ali; Rahman, AFM Mustafizur; Hasan, Choudhury M; Chowdhury, AM Sarwaruddin (Dhaka University Journal of Science, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/dujs.v61i2.17073 Dhaka Univ. J. Sci. 61(2): 211-212, 2013 (July)